DAYA TERIMA SERTA NILAI GIZI COOKIES TEPUNG UBI JALAR UNGU DAN TEMPE SUBSTITUSI TEPUNG IKAN GABUS - HJ.Sukma Wati; Abdullah Thamrin; R. Sri Rahayu (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
ABSTRACTBackground. Utilization of purple sweet potato flour which is low on glycemic index and high in fiber and tempeh flour which is high in fiber is expected to provide additional nutritional value. Based on the potency of the two ingredients, namely sweet potato and tempeh, these two ingredients can be alternative ingredients in the manufacture of cookies / cookies.Destination. This study aims to determine how the acceptability and nutritional value of cookies with purple sweet potato flour and tempeh flour with snakehead fish meal substitution for Diabetes Mellitus patients.Method. This type of research is a kind of laboratory with a post test design research design. Acceptability was assessed based on the organoleptic test results of 25 panelists, then analyzed the nutritional content of protein and fiber.Result. The results of the research on acceptance of the aspects of color, aroma, texture and taste showed p value of 0.660, 0.524, 0.074 and 0.432 respectively, which meant that there was no significant difference.Conclusion. The best treatment is formula 3 with 15% mean value of 3.46. The protein content of the purple sweet potato flour and tempeh flour with substitution of heavy snakehead fish meal with a substitution of 15% by weight per 8 g contains 1.168 g protein. The fiber content of the purple sweet potato flour and tempeh flour with the substitution of snakehead fish meal with a substitution of 15% by weight per 8 g contains 2.2598 g of fiber.Suggestion. For DM patients, 8 pieces of formula 3 cookies with a concentration of 15% can be consumed to meet protein needs and 2 pieces to meet fiber as a snack. For other researchers, it can increase the concentration of snakehead fish meal substitution and can analyze albumin levels.